Pemberian Penguatan Konsep Secara Tatap Muka Via Zoom Meeting dalam Pembelajaran Daring - Marni Zulyanty (Jurnal Tadris Matematika, 2021)
The spread of the disease that occurs throughout the world, namely the Covid-19 pandemic, has made changes to learning methods. The learning method is now carried out with online learning, which previously used the face-to-face method. However, there are many shortcomings occurred when using online learning method. One thing that is most highlighted regarding the shortcomings of online learning is the inability of students to understand the material, including learning mathematics. This study used a qualitative approach with the aim of describing the effect of giving face-to face concept reinforcement via zoom meetings on the success of online learning. The research instrument was the researcher and the interview guideline sheet. The subjects of the research are the 3rd semester students of Tadris Matematika UIN STS Jambi in the academic year of 2020/2021. The results showed that strengthening the concept via zoom meetings could be done through systematic dialogue so that the concept can be fully understood. The dialogue is an open dialogue and is very dependent on the response of students. Face-to-face strengthening of concepts in online learning through systematic dialogue via zoom meetings is proven able to make students understand the concepts being taught even though learning is done with online learning.